Discover the answers to your questions at Westonci.ca, where experts share their knowledge and insights with you. Join our platform to get reliable answers to your questions from a knowledgeable community of experts. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.

Solve the system: y = 12 + 4x y = -33 - 5x

Sagot :

The equation system is:

[tex]\begin{gathered} y=12+4x \\ y=-33-5x \end{gathered}[/tex]

So we can made the equation equal so:

[tex]\begin{gathered} 12+4x=-33-5x \\ 4x+5x=-33-12 \\ 9x=-45 \\ x=-\frac{45}{9} \\ x=-5 \end{gathered}[/tex]

Now we can replace the value of x to find y in the first equation so:

[tex]\begin{gathered} y=12+4(-5) \\ y=12-20 \\ y=-8 \end{gathered}[/tex]

so the solution is:

[tex](-5,-8)[/tex]